Social identity and support for counteracting tobacco company marketing that targets vulnerable populations - Baig, Sabeeh A. (Soc Sci Med, 2017)
RATIONALE: Tobacco companies use advertising to target vulnerable populations, including youth, racial/ethnic minorities, and sexual minorities. OBJECTIVE: We sought to examine how personal identity affects support for population-specific anti-smoking advertisements that could serve as countermeasures to industry practices. METHODS: In 2014–2015, we surveyed probability phone samples of adults and adolescents (n = 6,139) and an online convenience sample of adults (n = 4,137) in the United States. We experimentally varied the description of tobacco industry marketing practices (no description, general, or specific to a target group). The four prevention target groups were teens; African Americans; Latinos; and gays, lesbians, and bisexuals (GLBs). Participants were either members or non-members of their prevention target group. RESULTS: Support was highest for anti-smoking advertisements targeting teens, moderate for Latinos and African Americans, and lowest for GLBs. In-group members expressed higher support than out-group members when anti-smoking advertisements targeted African Americans, Latinos, and GLBs (all p < .05). However, when teens were the target prevention group, in-group members expressed lower support than out-group members (p < .05). The description of industry marketing practices did not have an effect. Results were similar across the phone and online studies. CONCLUSIONS: Our findings suggest that the public strongly supports advertisements to prevent smoking among teens, but support for similar efforts among other vulnerable populations is comparatively low. Anti-smoking campaigns for vulnerable populations may benefit from a greater understanding of the role of social identity in shaping public support for such campaigns.